Safe Haven Currencies - Žáková, Bianka; Taušer, Josef; Zezula, Jakub; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
Although various studies with the pivotal point on safe haven currencies have been conducted throughout the last few decades, the attention of academics has been paid to diverse attributes of safe haven currencies. Thus, there has been no systematic research focusing on how turbulent times such are the spread of the highly infectious virus known as Covid-19 and the escalated armed conflict between Russia and Ukraine influenced the traditional safe haven currencies and how their roles differentiated during these geopolitical events. Therefore, this master`s thesis addresses a phenomenon known as safe haven currencies amid these enumerated geopolitical crises. Under the expression of safe haven currencies, it is comprehended hard currencies such as the Swiss franc, euro, American dollar, and Japanese yen. In this master’s thesis, we scrutinise whether, during these two global unprecedented occurrences, the adduced national tenders exhibited characteristics of safe haven assets. To analyse their behaviours, we first examine and compare macroeconomic figures among the currencies under review. Secondly, we analyse and discuss the relevance of the energy shock on the currencies, especially as a consequence of imposed sanctions against the Russian Federation. Subsequently, we utilise quantitative analytical methods, comprising descriptive and inferential statistics, to identify which of the observed national tenders demonstrated the behaviour of a safe haven asset. Lastly, we employ a qualitative approach in the form of a semi-structured interview with an expert from the finance sector who contributed meaningfully to the comprehension of various aspects linked to safe haven currencies.
Thus, this master’s thesis provides valuable insights not only for investors but also for managers and policymakers to expand their understanding of safe haven currencies and subsequently contribute to a more profound comprehension of what function the scrutinised currencies played during the enumerated geopolitical crises which improve their ability to mitigate risk emerging from currencies’ volatility. Our research reveals that the Swiss franc and the euro exhibited the behaviour of safe haven currencies during the Covid-19 pandemic whereas, amidst the escalated military conflict, the market perceived the Swiss franc and the US dollar as prominent safe haven assets.
Vedoucí práce: Josef Taušer
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses